Management Tools to Reduce Carnivore-Livestock Conflicts: Current Gap and Future Challenges - Zorondo-Rodriguez, F (Elsevier Inc., 2018)
Predation on domestic animals by carnivores is a persistent problem wherever carnivores and livestock co-occur. A wide range of management tools to reduce predation has been invoked. However, the evidence of their effectiveness is still limited for a broader range of species and conditions. Using a global analysis of domestic animal predation by native carnivores under a “before-after/control-impact” framework, we assessed the effectiveness of management techniques used to reduce domestic animal predation identifying knowledge gaps and research needs. We reviewed 291 predation cases in 149 studies published between 1990 and 2017 involving 47 carnivores. Lethal control is the most common method to reduce predation in comparison with nonlethal techniques. Yet the effectiveness of both approaches remains poorly evaluated (30.1% of study cases) and largely based on producers’ perceptions (70% of cases where effectiveness was evaluated). Lethal control and night confinement of domestic animals would have no effect on reducing predation, whereas the use of livestock-guarding dogs, fencing, or herdsmen may significantly reduce domestic animal losses. When the effectiveness of each technique to reduce predation was assessed by large and mesocarnivores, fencing significantly reduced predation of domestic animals by the former. Despite little scientifically published material, our findings indicate lethal control would have no effect in reducing animal predation by native carnivores when compared with nonlethal techniques. Our study also indicates the effectiveness may vary depending on the type of carnivore involved in the conflict with livestock activity. The use of an evidence-based framework to measure and assess the differential effectiveness of nonlethal techniques and the use of complementary tools at different spatial and temporal scales must be research priorities to prevent livestock predation while promoting the conservation of carnivores in production-oriented lands as encouraged by the Convention of Biological Diversity. © 2018 Elsevier Inc.
Keywords: carnivora; carnivore management; human-wildlife conflicts; livestock predation; production-oriented lands